2007
DOI: 10.1590/s1413-86702007000200009
|View full text |Cite
|
Sign up to set email alerts
|

Salivary anti-PGL IgM and IgA titers and serum antibody IgG titers and avidities in leprosy patients and their correlation with time of infection and antigen exposure

Abstract: The present work proposed to correlate serum antibody avidity and salivary antibody titers as parameters for time of infection and antigen exposure in a co-hort study evaluating leprosy patients in different periods of treatment. Colorimetric enzyme-immunoassays for salivary antibodies, serum antibody IgG titers and avidities were performed in the samples. Anti-PGL-1 IgA and IgM salivary antibodies were significantly higher in multibacillar (MB-L) patients compared to normal controls (p<0.05), but not when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
0
19
1
1
Order By: Relevance
“…7 An interesting finding is the differential expression of IgA in L-lep versus T-lep lesions. Anti-M. leprae IgA has been previously reported in salivary secretions of leprosy patients, 32 and the presence of IgA as well as IgG and IgM has previously been identified from induced blisters over skin lesions from patients with L-lep and ENL. 33 Here, we found a correlation of both the messenger RNA and protein levels of IgA, with L-lep versus T-lep directly in skin lesions, suggesting a role for antibodies including promoting progressive infection.…”
Section: Effect Of Il-5 On M Leprae Activation Of B Cellsmentioning
confidence: 95%
“…7 An interesting finding is the differential expression of IgA in L-lep versus T-lep lesions. Anti-M. leprae IgA has been previously reported in salivary secretions of leprosy patients, 32 and the presence of IgA as well as IgG and IgM has previously been identified from induced blisters over skin lesions from patients with L-lep and ENL. 33 Here, we found a correlation of both the messenger RNA and protein levels of IgA, with L-lep versus T-lep directly in skin lesions, suggesting a role for antibodies including promoting progressive infection.…”
Section: Effect Of Il-5 On M Leprae Activation Of B Cellsmentioning
confidence: 95%
“…In addition, it has been shown that MDT seems to reduce anti‐PGL1 antibody levels (Bonfitto et al , ; Rosa et al , ). Similarly, Nagao‐Dias et al () demonstrated that salivary anti‐PGL‐1 IgA and IgM antibodies were significantly higher in MB patients compared with normal controls, but not when compared with PB patients. Moreover, the same authors found a good correlation between salivary anti‐PGL‐1 IgA and IgM levels in MB patients (Nagao‐Dias et al , ).…”
Section: Detection Of Leprosy Antibodies: Salivary Biomarkersmentioning
confidence: 88%
“…As it has been shown in previous studies, lipid antigen may elicit ingested by phagocytes. 38 As the presence of anti-PGL1 IgG has been demonstrated in leprosy patients 28 and in contacts, 14 we have decided in the present work to evaluate anti-PGL1 IgA titers.…”
Section: Discussionmentioning
confidence: 99%
“…Serological analyses for anti‐PGL1 antibodies were performed according to the procedure described elsewhere, with some modifications. Ninety‐six well flat‐bottom microplates (code 3590, Costar, USA) were coated with 5 mg/L of native PGL‐1 in absolute ethyl alcohol (50 μL per well), kindly donated by the Bei Resources/ATCC (Manassas, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation